Talking about mindfulness: An ethnography of communication analysis of two speech communities. (July 2019) - Stofleth, Daniel; Manusov, Valerie
Abstract: Mindfulness as a concept and practice has gained significant recognition, referenced and employed in both academic studies and the popular press. Broad conclusions are drawn about its relationships to other variables and its impacts or benefits. Taking an Ethnography of Communication approach, we perform a communication codes analysis on two speech communities (popular press articles and academic journal articles) to determine what each references when writing about 'mindfulness.' Academic articles were more likely to include explicit definitions, tending to include both 'attention' and 'awareness'; popular article definitions emphasized awareness only and referenced the religious basis of mindfulness. Both academic and popular articles conflate mindfulness with meditation and delineate what it is not to offer more emphasis on what it is. Highlights: Academic communication is more likely than the popular press to define mindfulness. The popular press more often invokes the religious basis of mindfulness. An effort is made to "normalize" mindfulness in popular discourse. The academic community appears more comfortable with science-based language.